Hematocrit, age, and survival in a wild vertebrate population. Issue 1 (21st December 2020) - Brown, Thomas J.; Hammers, Martijn; Taylor, Martin; Dugdale, Hannah L.; Komdeur, Jan; Richardson, David S.
Abstract: Understanding trade‐offs in wild populations is difficult, but important if we are to understand the evolution of life histories and the impact of ecological variables upon them. Markers that reflect physiological state and predict future survival would be of considerable benefit to unraveling such trade‐offs and could provide insight into individual variation in senescence. However, currently used markers often yield inconsistent results. One underutilized measure is hematocrit, the proportion of blood comprising erythrocytes, which relates to the blood's oxygen‐carrying capacity and viscosity, and to individual endurance. Hematocrit has been shown to decline with age in cross‐sectional studies (which may be confounded by selective appearance/disappearance). However, few studies have tested whether hematocrit declines within individuals or whether low hematocrit impacts survival in wild taxa. Using longitudinal data from the Seychelles warbler ( Acrocephalus sechellensis ), we demonstrated that hematocrit increases with age in young individuals (<1.5 years) but decreases with age in older individuals (1.5–13 years). In breeders, hematocrit was higher in males than females and varied relative to breeding stage. High hematocrit was associated with lower survival in young individuals, but not older individuals. Thus, while we did not find support for hematocrit as a marker of senescence, high hematocrit is indicative of poor condition in younger individuals. Possible explanations are that these individuals were experiencing dehydration and/or high endurance demands prior to capture, which warrants further investigation. Our study demonstrates that hematocrit can be an informative metric for life‐history studies investigating trade‐offs between survival, longevity, and reproduction. Abstract : Using long‐term data we investigated the association between haematocrit, longitudinal age and survival in a wild vertebrate population—the Seychelles warbler ( Acrocephalus sechellensis ). Haematocrit exhibited a distinctive age‐dependent pattern within‐individuals, and young individuals with high haematocrit had poorer survival prospects. This study highlights a novel physiological change with age that is indicative of individual condition in wild populations.